EFFECT OF RESAM FIBER ADDITION (Dicranopteris Linearis) ON THE CHARACTERISTICS OF CONCRETE - Itteridi, Vike; Bareski, Nopen; Edowinsyah, Edowinsyah (Fakultas Teknik Universitas Tanjungpura, 2023)
This study discusses the effect of the addition of resin fibers (Dicranopteris linearis) on the characteristics of concrete. The purpose of fibers to the characteristics of concrete. horns, anti-termite, not easily broken and resistant to humid air and is a plant that grows a lot in Pagar Alam City area. Therefore, the researchers decided to examine the effect of adding resin rod fibers to the characteristics of concrete. characteristics of this concrete is an experimental method that is tested, namely the physical material test, slump test, compressive and flexural strength of concrete. Experiments with the addition of resin rod fibers to the concrete mix of 0.5% of the weight of normal concrete cement. All samples were tested at the age of 3,7,14,21 and 28 days. Based on the test results, 3 cm and 5 cm long resin fibers were used. At 3 cm compressive strength of 28 day old concrete decreased by 0.36% from normal concrete with flexural strength increased by 0.02% of normal concrete while at 5 cm compressive strength of 28 day old concrete decreased by 0.66% of concrete normal while the flexural increase as much as 0.04% of normal concrete. The decrease in compressive strength is due to the addition of impregnated fibers into the concrete which will create more voids or voids in the concrete, the reduced density of concrete and disruption of the bond between cement and other concrete aggregates and the increase in flexural strength is caused because the resin fibers play a role in resisting cracks due to the pressure exerted by them. occurs in the concrete so as to increase the flexural strength of the concrete.